Degenerate Moments and Expectation of Monomials (European Journal of Pure and Applied Mathematics, 2024)
The aim of this paper is twofold. Firstly, we obtain expressions of the degenerate moments of a discrete nonnegative integer valued random variable. Secondly, we get an expression for the expectation of any monomial in  discrete nonnegative integer-valued random variables.
Keywords: degenerate moments; expectation of monomials; discrete nonnegative integer-valued random variables.